Pengembangan Kurikulum Merdeka Belajar Kampus Merdeka (MBKM) untuk Meningkatkan Daya Saing Mahasiswa di UIN Sayyid Ali Rahmatullah Tulungagung - Hawwin Muzakki (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2023)
UIN Sayyid Ali Rahmatullah Tulungagung has implemented the MBKM curriculum, one of the strategies to increase student competitiveness. One of the aspects developed to improve student competitiveness is the ability of soft skills, hard skills, intrapersonal intelligence, and interpersonal intelligence. It is interesting to see the curriculum development using the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model lens. Using a descriptive qualitative approach with the type of case study research, this research explores how to analyze, design, develop, implement, and evaluate the development of the MBKM Curriculum at UIN SATU Tulungagung. In conclusion, the analysis aspects of the MBKM curriculum are: analyzing the Vision and Mission, reading industry needs, global capabilities, and learning objectives. The MBKM curriculum design is 4 semesters of learning in Study Programs, 1 semester of Learning outside the Study Program in Higher Education, 2 semesters of learning outside of Higher Education, then 1 semester of Final Project. The development of the MBKM Curriculum at UIN Sayyid Ali Rahmatullah Tulungagung includes 8 BKP (Forms of Learning Activities) to improve hard skills. Soft skills, interpersonal skills, and intrapersonal skills. Implementing the MBKM Curriculum is carried out in stages. It continues until semester 6 through the Permata PTKIN program evaluation of the MBKM curriculum: sharing with users, student feedback, and direct observation.